A review on bi/polymetallic catalysts for steam methane reforming - Wang, Siqi; Nabavi, Seyed Ali (Elsevier, 2023)
Blue hydrogen production by steam methane reforming (SMR) with carbon capture is by far the most commercialised production method, and with the addition of a simultaneous in-situ CO2 adsorption process, sorption-enhanced steam methane reforming (SESMR) can further decrease the cost of H2 production. Ni-based catalysts have been extensively used for SMR because of their excellent activity and relatively low price, but carbon deposition, sulphation, and sintering can lead to catalyst deactivation. One effective solution is to introduce additional metal element(s) to improve the overall performance. This review summarizes recent developments on bi/polymetallic catalysts for SMR, including promoted nickel-based catalysts and other transition metal-based bi/polymetallic materials. The review mainly focuses on experimental studies, but also includes results from simulations to evaluate the synergistic effects of selected metals from an atomic point of view. An outlook is provided for the future development of bi/polymetallic SMR catalysts.
Keywords: Metallic catalysts; Alloy; Steam methane reforming; Sorption-enhanced steam methane reforming; Hydrogen production; Syngas